Vitamin D Receptor-Mediated Upregulation of CYP3A4 and MDR1 by Quercetin in Caco-2 cells - Chae, Yoon-Jee; Cho, Kwan Hyung; Yoon, In-Soo; Noh, Chi-Kyoung; Lee, Hyo-Jong; Park, Yohan; Ji, Eunhee; Seo, Min-Duk; Maeng, Han-Joo (Planta Medica, 2016)
To examine whether quercetin interacts with vitamin D receptor, we investigated the effects of quercetin on vitamin D receptor activity in human intestinal Caco-2 cells. The effects of quercetin on the expression of the vitamin D receptor target genes, vitamin D3 24-hydroxylase, cytochrome P450 3A4, multidrug resistance protein 1, and transient receptor potential vanilloid type 6 were measured using quantitative polymerase chain reaction. The vitamin D receptor siRNA was used to assess the involvement of the vitamin D receptor. Vitamin D receptor activation using a vitamin D responsive element-mediated cytochrome P450 3A4 reporter gene assay was investigated in Caco-2 cells transfected with human vitamin D receptor. We also studied the magnitude of the vitamin D receptor activation and/or synergism between 1α,25-dihydroxyvitamin D3 [1,25(OH)2D3] and quercetin-like flavonoids. Slight but significant increases in the mRNA expression of cytochrome P450 3A4, vitamin D3 24-hydroxylase, multidrug resistance protein 1, and transient receptor potential vanilloid type 6 were observed after 3 days of continual quercetin treatment. The silencing effect of vitamin D receptor by vitamin D receptor siRNA in Caco-2 cells significantly attenuated the induction of the vitamin D receptor target genes. Moreover, quercetin significantly enhanced cytochrome P450 3A4 reporter activity in Caco-2 cells in a dose-dependent manner, and the expression of exogenous vitamin D receptor further stimulated the vitamin D receptor activity. Quercetin-like flavonoids such as kaempferol stimulated the vitamin D receptor activity in a manner similar to that seen with quercetin. Taken together, the data indicates that quercetin upregulates cytochrome P450 3A4 and multidrug resistance protein 1 expression in Caco-2 cells likely via a vitamin D receptor-dependent pathway.
Keywords: multidrug resistance protein 1; P-glycoprotein; cytochrome P450 3A4; Caco-2 cells; quercetin; 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3); vitamin D receptor